Teaching Note—Nonprofit Websites and the Engagement Competency of Social Work Education. (2nd July 2020) - Twis, Mary K.; Hoefer, Richard
ABSTRACT: Nonprofits' engagement with stakeholders ensures their existence since engagement guarantees support for the organization. Social work researchers, leaders, and educators must consider engagement within the context of geographic and online communities. Indeed, learning how to engage with individuals and communities is a core competency within social work education. We believe that it is important to interpret this competency as a mandate for educators who are preparing social work students for nonprofit leadership roles in an online society. After introducing this perspective, we segue into a discussion of our findings from a study of 145 nonprofits' websites. Findings suggest that there are opportunities for nonprofit leaders to enhance stakeholder engagement through their website designs; we discuss implications for social work education.